Safety and effectiveness of fondaparinux as a postpartum thromboprophylaxis during puerperium among muslim women: A single centre prospective study - Muhamad, Normaliza; Abu, Muhammad Azrai; Kalok, Aida Hani; Shafiee, Mohd Nasir; Shah, Shamsul Azhar; Ismail, Nor Azlin Mohamed (Frontiers in Pharmacology, 2022)
Background: Venous thromboembolism (VTE) remains one of the leading causes of maternal morbidity and mortality, with postpartum period carrying the greatest risk. Perinatal thromboprophylaxis is often administered based on risk-factor assessment. Low molecular weight heparin has a proven safety profile in the obstetrics population, however, its porcine-derived content may lead to reduced uptake amongst certain religious groups. We aimed to evaluate the safety of fondaparinux as an alternative postpartum thromboprophylaxis. Methods: We conducted a prospective, single arm, open label study from September 2017 until March 2018. Women who fulfilled the criteria for post natal thromboprophylaxis based on the 2015 RCOG guidelines were recruited. Each patient received subcutaneous injection of Fondaparinux, 2.5 mg daily for 10 days. A telephone interview was conducted on day 10 post delivery. Each woman was subsequently reviewed in the outpatient clinic 6 weeks postpartum. The primary outcome measure was occurrence of pulmonary embolism or deep vein thrombosis suggestive by clinical symptoms and assessment. Secondary outcome measures were allergic reaction and bleeding tendency such as secondary post-partum haemorrhage, spinal site bleeding and wound haematoma. Allergic reaction and bleeding tendency in neonates were also recorded. Results: Sixty women were included in the analysis. There were no VTE cases amongst our cohort. No major bleeding was recorded. Two patients (3.3%) had wound haematoma, one of which occurred 3 weeks post delivery. No adverse effect in neonates was noted. Conclusion: Fondaparinux is a safe alternative thromboprophylaxis for postpartum women.